Construction of new country image through film media: Chinese films from 1949 to 1978 (Herald of Journalism, 2020)
This article analyzes the film producer groups in mainland China from 1949 to 1978, and explores the social, political, and economic roots behind the text. It involves 30 films and 45 filmmakers.The academic significance of this article is to analyze the historical film narrative to explain the deep-seated reasons for the critical-affirmative-critical process of film narrative after the founding of New China. The most important reason is the political needs. The practical significance is to provide a refer-ence for film producers in a narrative direction. More complex social backgrounds must be considered.This article mainly studies the common social attributes of film producers through their group re-search. At the same time, a structuralist film narratology approach was used. For example, the methods of Propp, Todorov, Strauss, and Grams. Analyze the social structural features behind the film narrative from different aspects.The conclusion of the study is that film narrative completes the construction of a national image by establishing the core position of the Communist Party in the establishment of a new country. After the founding of New China, the legitimacy of the Communist Party of China needs to be widely recognized by society. The film medium was a form of communication that was well suited to the conditions at the time. The supreme ruler hopes to quickly build a common imagination of the country’s image through the repeated narration of the film. The value of the research is to analyze the film narrative for the first time by analyzing the group characteristics of the film producers themselves.
Keywords: national image, media, cinematography, communist party, China.